Monitoring Extreme Impacts of Rugulopteryx okamurae (Dictyotales, Ochrophyta) in El Estrecho Natural Park (Biosphere Reserve). Showing Radical Changes in the Underwater Seascape - García-Gómez, José Carlos; Florido, Marta; Olaya-Ponzone, Liliana; Rey Díaz de Rada, Jorge; Donázar-Aramendía, Iñigo; Chacón, Manuel; Quintero, Juan José; Magariño, Salvador; Megina, César (Frontiers in Ecology and Evolution, 2021)
The invasive macroalga Rugulopteryx okamurae represents an unprecedented case of bioinvasion by marine macroalgae facing the European coasts. Since the first apparition of the species in the Strait of Gibraltar in 2015, its fast dispersion along the introduced habitats constitutes a real challenge to develop monitoring strategies that ahead of its impacts. The present study uses three different approaches to address impacts on the benthic ecosystems, at the same time offers relevant data for future management actions in El Estrecho Natural Park (PNE). Information obtained by monitoring permanent sentinel stations revealed a significant loss in resident species coverage after the moment of maximum growth in 2017. Thus, despite coverage of R. okamurae did not strongly varied in the latter years, impacts generated remain high in the habitats studied. Estimations of the invasive species coverage by combining cartographic image analysis and in situ data predicted a major occupation (over 85% coverage) between 10 and 30 meters, coinciding with the maximum rocky surface areas (m2) mapped on the PNE. Furthermore, a Citizen Science research collaboration evidenced impacts on the benthic seascape through an ad hoc exploration of images that allowed a "before" and "after" comparison of the invasion process in the same geographic locations. This has made it possible to graphically demonstrate severe changes in the underwater seascape and, therefore, the general impact of this new biological invasion. The spatial colonization estimations combined with the impacts reported by both scientific (SBPQ sentinel stations) and civilian (Citizen Science) monitoring methodologies claim the urgent development of further studies that allow the design of monitoring strategies against R. okamurae expansion across the Mediterranean and Atlantic waters.